Synthesis and characterization of Aluminium and zinc-based aminoterephthalate (Al-ATA and Zn-ATA) metal-organic frameworks for enhanced gas adsorption and separation - Sadiq, Abubakar Chadi; Mohmmad, Mainta; Adamu, Usman Abubakar (PUI BiGME Universitas Jambi, 2025)
Metal-organic frameworks (MOFs) have emerged as highly promising materials for gas sorption and separation, owing to their extensive surface areas, customizable pore sizes, and diverse structural properties. This study delves into the mechanisms of gas sorption, strategies for gas separation, and synthesis methodologies of MOFs, with a particular focus on (M=Al, Zn) with aminoterephthalate. The synthesis of these MOFs involves the reaction of metallic salts with 2-amino-terephthalic acid under mild solvothermal conditions, using an ethanol and water solvent mixture. The synthesized MOFs samples were characterized using techniques such as FTIR, SEM, EDX, XRD, BET, and TGA to determine functional groups, surface morphology, elemental analysis, molecular structure, pore sizes, surface areas, and thermal stability respectively. The findings underscore the potential of MOFs such as Zn-amino terephthalate exhibits high CO2 uptake capacities at low temperature while at high temperature reduces the affinity for CO2 and adsorbed CH4 higher compared to Al-amino terephthalate, at various temperatures range (30°C, 60°C, and 100°C) and 1.0 bar pressure of the findings are consistent across various studies.